ANALYSIS OF INCOME AND WELFARE OF OIL PALM FARMERS IN TANJUNG PASIR VILLAGE SOUTH KUALUH DISTRICT NORTH LABUHANBATU REGENCY - Prayoga, Yudi; Harahap, Fitra Syawal (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
this study aims to analyze: oil palm farming income, household income, household income allocation, the proportion of household food consumption expenditure, the proportion of household non-food consumption expenditure, and the level of welfare of households oil palm farmers. The research was carried out in May-June 2024 in Tanjung Pasir Village, South Kualuh District, North Labuhanbatu Regency. The population of this study was 62 people with a sample of 38 people using Slovin Formula taken at Simple Random. Data analysis used is qualitative and quantitative descriptive analysis. The results showed income from oil palm farming an average of Rp 5,779,825 / month. Household income comes from oil palm farming, other farming, non-farming, and income from household members. The average household income is Rp 8,607,017 / month. The allocation of household income to food needs per month amounted to Rp 1,324,421 or 15.35% and non-food needs amounted to Rp 7,282,596 or 84.61%. The proportion of household food consumption expenditure per month of 15.39% means that 15.39% of household expenditure is allocated to food. The proportion of non-food consumption expenditure of households per month is 84.61%, which means that 84.61% of household expenditure is allocated for non-food expenditure. Based on the proportion of food consumption (PKP) and the proportion of non-food consumption (PKNP) of oil palm farmer households, it is concluded that the level of welfare of oil palm farmer households in Tanjung Pasir Village, South Kualuh District, North Labuhanbatu Regency is classified as a prosperous household.